(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2024)
The main purpose of this article is to analyse the public policies that were implemente don gender an violence against women in the Province of Neuquén since the formation of the Family Violence Prevention and Assitance Service in Neuquén, later with the sanction of the first Family Violence Prevention Law that was achieved 10 years later, in 1997 until the inauguration of the first shelter for women in situacions of violence (1987-2004). The study is based on the testimonies of its protagonists, jounalistic archives of the interviewees and media that were analyzed in depth with the support of a qualitative methology and feminist epistemology that allowed us to visualize the struggles and achievements of those who were at the forefront of these processes. The article focuses on higlhlighting the progres an difficulties in te implementation of the aforementioned public policies.